A close-pair binary in a distant triple supermassive black hole system. - Deane, R; Paragi, Z; Jarvis, M; Coriat, M; Bernardi, G; Fender, R; Frey, S; Heywood, I; Klöckner, H; Grainge, K; Rumsey, C (Nature Publishing Group, 2014)
Galaxies are believed to evolve through merging, which should lead to some hosting multiple supermassive black holes. There are four known triple black hole systems, with the closest black hole pair being 2.4 kiloparsecs apart (the third component in this system is at 3 kiloparsecs), which is far from the gravitational sphere of influence (about 100 parsecs for a black hole with mass one billion times that of the Sun). Previous searches for compact black hole systems concluded that they were rare, with the tightest binary system having a separation of 7 parsecs (ref. 10). Here we report observations of a triple black hole system at redshift z = 0.39, with the closest pair separated by about 140 parsecs and significantly more distant from Earth than any other known binary of comparable orbital separation. The effect of the tight pair is to introduce a rotationally symmetric helical modulation on the structure of the large-scale radio jets, which provides a useful way to search for other tight pairs without needing extremely high resolution observations. As we found this tight pair after searching only six galaxies, we conclude that tight pairs are more common than hitherto believed, which is an important observational constraint for low-frequency gravitational wave experiments.